The Role of Information System Management For Educational Institutions During Pandemic - Muhammad Syarwani; Syahrani Syahrani (Indonesian Journal of Education (INJOE), 2022)
In the world of education technology is very important, because nowadays almost every activity uses technology. One of them is information technology in order to store student data such as student biodata, teacher biodata, new student admissions data, attendance lists, alumni bios, addresses, educational history, teacher attendance lists and others, which can be viewed through the management information system. With a management information system, it can support the learning process, especially during the covid 19 pandemic. The pandemic forces the learning process to use technology. The government together with the Ministry of Education and Culture work together to meet the needs of technology in education, especially in Indonesia. The management information system has an impact on improving the quality of the school towards a better direction, it is also useful in managerial decisions that will be taken by the school.